2019
DOI: 10.1051/kmae/2019001
|View full text |Cite
|
Sign up to set email alerts
|

An epilimnion and hypolimnion temperature model based on air temperature and lake characteristics

Abstract: Water temperature is an essential ecological variable that influences life beings at several organizational levels, but its monitoring at the regional level is costly. An alternative is using models, which summarise the knowledge of the functioning of the system so that they can be used to answer specific questions. We present a model to calculate the epilimnion and hypolimnion temperature of inland water bodies based on air temperature and on their geographical and morphological characteristics. The seven mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 108 publications
3
35
0
Order By: Relevance
“…The model has been testified efficient in different regions [33] [34]. However, the original air2water is limited to simulate the surface temperature of open water, which results in difficulties for applications in lakes with long ice cover duration.…”
Section: B Methods 1) Modified Air2water Modelmentioning
confidence: 99%
“…The model has been testified efficient in different regions [33] [34]. However, the original air2water is limited to simulate the surface temperature of open water, which results in difficulties for applications in lakes with long ice cover duration.…”
Section: B Methods 1) Modified Air2water Modelmentioning
confidence: 99%
“…Two stressors were considered: temperature and eutrophication. Because water temperatures were not available for all the lakes but are strongly correlated with air temperatures [71,72] (R 2 = 0.82), we used the latter to characterize lake temperatures. To this end we used data from the SAFRAN reanalysis [73,74], available at a spatial resolution of 8 km × 8 km.…”
Section: Environmental Datamentioning
confidence: 99%
“…The proposed method could be used, above all, in hydrobiological research, as an alternative to models to calculate the water temperature of inland water bodies, such as e.g., presented by [81], parameterized by using official monitoring data and the satellite temperature data, model, which is based on air temperature and on their geographical and morphological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Ptak et al [32] showed that the course of the average annual water temperature in the years 1972-2016 indicates its clear warming, closely corresponding to the air temperature. Air temperature time series have also been used many times to construct models describing water temperature changes [18], e.g., Prats and Danis [81] published a model for calculating the epilimnion and hypolimnion temperature of inland waters on the basis of air temperature, as well as geographic and morphological features of these lakes.…”
mentioning
confidence: 99%